Religious Education Model for Indigenous Children in Malaysia: An Ethnographic Study - Mutathahirin Mutathahirin; Sobariah Abu Bakar; Razita Razita; Rashidi Abbas; Nuha Sufina Binti Saidi (Muaddib: Journal of Islamic Teaching and Learning, 2026)
Program Pembangunan Tamadun Masyarakat Asli (PETAMA) established by Yayasan Pahang in 1998, was designed to cultivate knowledgeable and capable leaders among Malaysia’s Indigenous Peoples, enabling them to achieve parity with other ethnic groups. PETAMA graduates are expected to serve as da’i and spiritual guides within their communities. This study investigates the religious and educational approaches applied in PETAMA to enhance the quality of life and spiritual awareness of the Indigenous Children subgroup of Malaysia’s Indigenous Peoples. Using a qualitative ethnographic design, data were collected through in-depth individual and group interviews with 30 PETAMA students from the Indigenous Children community. Thematic analysis was conducted using NVivo12 software. Findings reveal ten key approaches: i) formal religious education, ii) religious activities, iii) training and development of da’i, iv) spiritual counseling and mentoring, v) application of Islamic values in daily life, vi) collaboration with religious institutions, vii) formal education, viii) moral and religious education, ix) educational technology and innovation, and x) academic mentoring. These findings provide initial empirical insights into the role of PETAMA in shaping religious education among Indigenous children in Malaysia and serve as a foundation for future research on indigenous education, cultural integration, and spiritual development.